PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING DALAM MENGALIHWAHANAKAN HIKAYAT KE CERPEN SISWA KELAS X DI SMA SANTO PETRUS MEDAN TAHUN PEMBELAJARAN 2024/2025 - Silalahi, Anzelina; Liana; Candra Ronitua Gultom (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the guided inquiry learning model on students' ability to transform hikayat into modern short stories. This research employed a quantitative approach with an experimental method and used a One Group Pretest-Posttest Design. The sample consisted of 31 students from class X-2 at SMA Santo Petrus Medan in the academic year 2024/2025. The instruments used were tests (pretest and posttest) and a student perception questionnaire, both validated by experts. The normality test results showed that the data were normally distributed, with significance values of 0.60 > 0.05 for the pretest and 0.75 > 0.05 for the posttest. The average pretest score was 64.22, which increased to 82.25 in the posttest, showing a gain of 18.03 points. The questionnaire results showed an average score of 4.4 out of 5, categorized as very high, indicating a highly positive response from students. The t-test analysis revealed that the t-count (8.027) was greater than the t-table (1.697), with a significance level of 0.000 < 0.05. Therefore, the alternative hypothesis (H₁) is accepted, and the null hypothesis (H₀) is rejected, which indicates that the guided inquiry learning model significantly affects students’ ability to transform hikayat into short stories.